Development of a parallelised fluid solver for problems with mesh interfaces and deforming domains. (30th May 2018) - Aguerre, Horacio J.; Márquez Damián, Santiago; Gimenez, Juan M.; Nigro, Norberto M.
Highlights: A parallelised dynamic mesh strategy is proposed using OpenFOAM(R). The new strategy can address conservatively partially-overlapped interfaces. Large deformations are solved with the combination of layering and mesh deformation. The parallel implementation has shown an efficiency higher than 85%. Robustness and convergence are proved solving an internal combustion engine. Abstract: Numerical simulation of piston–cylinder problems such as internal combustion engines suffers from two difficulties related to discretization: the non-matching interfaces between cylinder and ports and the large deformation of the cylinder region. In this context, this paper presents a parallelized computational strategy, based on the Finite Volume method, where the mentioned issues are overcome. The non-matching discretization between regions is addressed with a new methodology which integrates the Arbitrary Coupled Mesh Interface (ACMI) method with the pseudo-supermesh approach to couple conservatively mesh interfaces with partial overlapping. For the large cylinder deformations, a layer addition/removal strategy is enhanced with mesh deformation to improve the handling of the mesh resolution. All methodologies are integrated and implemented for parallel computing obtaining a good scalability and computational efficiency. Specific examples are solved to analyse the performance of the new interface method and layering working separately and finally, the combination of both strategies is tested solving an internal combustion engine problem where the robustness of this dynamic mesh proposal is evaluated.